2013
DOI: 10.1190/geo2012-0199.1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical mode decomposition for seismic time-frequency analysis

Abstract: Time-frequency analysis plays a significant role in seismic data processing and interpretation. Complete ensemble empirical mode decomposition decomposes a seismic signal into a sum of oscillatory components, with guaranteed positive and smoothly varying instantaneous frequencies. Analysis on synthetic and real data demonstrates that this method promises higher spectral-spatial resolution than the short-time Fourier transform or wavelet transform. Application on field data thus offers the potential of highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(75 citation statements)
references
References 34 publications
0
74
0
1
Order By: Relevance
“…This paper is not going to cover the basic principles of HHT which have been introduced in much of the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. We will focus only on mode mixing problems of the EMD method in HHT.…”
Section: Mode Mixing Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is not going to cover the basic principles of HHT which have been introduced in much of the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. We will focus only on mode mixing problems of the EMD method in HHT.…”
Section: Mode Mixing Problemmentioning
confidence: 99%
“…Zhou et al demonstrated the new insights of EMD and HHT which can be used with seismic reflection data [13]. Xue et al used the three EMD-based analysis methods to perform a comparative study on hydrocarbon detection [14]. Han et al used EMD for seismic time-frequency analysis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The EMD based approach is widely used in audio signal processing [12,13], computational neuroscience [14], climate signal analysis [15], image processing [16], seismic signal [17] and biomedical signal processing [18]. This study focuses on the application of EMD in advanced speech signal processing including fundamental frequency estimation [19], voiced/unvoiced speech classification [20] and speech enhancement [21,22].…”
Section: Empirical Mode Decomposition (Emd) Is Newlymentioning
confidence: 99%
“…In oceanography, a combination of baroclinic modes helps model density profiles of seasonal cycles and other geophysical phenomena such as thermal or solar variation [23,64]. Similarly, in seismology, modes with differing frequency components help highlight different geological and stratigraphic information [35]. In holography, mode decomposition allows reducing speckle [46].…”
Section: Introductionmentioning
confidence: 99%